Estudio de mercado para la apertura de una sucursal de la Distribuidora Automotriz Quito (aceites, lubricantes y aditivos) en el sector centro de Latacunga con aplicación a las pymes - Caviedes Aguirre, Katherine Estefanía (2015)
This project develops the scheme creation of a branch of “Distribuidora Automotriz Quito”, in Latacunga's city; which distributes a range of products needed for all types of ground transportation nationwide, where most of the customers are from the Cotopaxi province and its best seller products are inside in the lubrication line and products that give the automotive performance as: oils, lubricants and additives. Different problems presented in the company are analyzed by not having branch: constant customer complaints by the late delivery of the merchandise, generating additional costs in the delivery, customer affluence to other distributors, which have caused the company decreases its sales, customer loses credibility in delivery dates, the company loses customers and profits decrease. Based on projected demand and supply in market research, it reflects a broader perspective of potential customers to be captured with the branch and the quantity of products to be sold with the opening of this new local; which will generate profits for the company. The project defines the legal context that the company must meet for the opening of the branch and the procedures to follow Finally, depending on the financial study stablishes how feasible or not implement the Project; concluding positively to the creation of the branch of “Distribuidora Automotriz Quito”.